Monitoring System Design Gravimetric Anesthetic Dose - Rika Wahyuni Arsianti; Adrian Premy Ashary; Kharis Hudaiby Hanif (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
Anesthesia is a very important step in surgery. Research on the fulfillment of the ideal criteria for anesthetic techniques continues. These inhalation anesthetics require slow induction times, are complex and expensive devices and cannot be performed if veterinary surgery is performed in the field. In this study, the technique used was anesthesia through gravimetric infusion. The purpose of this study was to monitor the dose of gravimetric infusion anesthesia using a load cell. The load cell sensor will send data to the NodeMCU to display the anesthetic dose that has been entered on the smartphone. The results of the gravimetric infusion anesthetic dose monitoring system produced a very small error of 0.004%. The error in reading the anesthetic dose is very important because the main factor of this gravimetric infusion anesthetic is the right dose to meet the criteria for ideal anesthesia.